The role of education and knowledge in the formation of a Malay proto-government - Muhammad Mustaqim Omar (2019)
This paper aims to investigate the role that education and knowledge played in the Malay formation of a proto-democratic government by studying and assessing the impact on the intellectual Malay landscape. Current scholarship on Malay nationalism is limited in the sense that it chooses to study the origins of Malay nationalism separately: that is, the clear delineation of Education and the rise of an intelligentsia. This paper will attempt to marry these 2 ideas, and in doing so, explore the impact of education and knowledge. The educated elites themselves engaged the public by first introducing new concepts which were required to form a proto-government. Secondly, these elites sought to regulate education while maintaining the integrity of Islam within the Malay People to maintain legitimacy. Lastly, this study will address how the perception of knowledge by Malays were changed following these reforms. Thus, this study will encapsulate the period of 1880-1930, in order to showcase how the Sultanate eventually gave way to a proto-democratic governance. Simultaneously, this period also features the explosion of contextualized foreign knowledge, making this period nearly perfect for this study.